Analisis Usahatani Pertanian Lahan Kering Melalui Integrasi Pertanian Dan Ternak Di Kabupaten Lombok Utara, Provinsi Nusa Tenggara Barat - Nuzuly Ilmia Cerminand; Ulfa Nurwiana; Mai Rizali (Yayasan Tajuk Indonesia, 2024)
The development of the agricultural sector is the mainstay of economic development. Empowerment of land resources as a basis for agricultural activities should receive more emphasis and attention from the government and other related parties. For this reason, strategic steps are needed to build public opinion and the government that dry land is the hope for the future of agricultural development to increase food security. The study used a descriptive method. The data collection technique used a survey technique. This study was conducted in North Lombok Regency, precisely in Bayan District, which was determine4d by